Asymptomatic bacteriuria and pyelonephritis during pregnancy - Y. L. Naboka; A. N. Rymashevsky; O. M. Kogan; I. A. Gudima; N. V. Vorobyeva; A. K. Alkina (Медицинский вестник Юга России, 2021)
The most common extragenital pathology during pregnancy is urinary tract infection (UTI) of various localization. In some cases, untreated UTI can contribute to the development of obstetric, urological, and perinatal pathologies. Factors predisposing to the UTI manifestation may include increased progesterone, delayed peristalsis, urine retention in the ureters, uterine growth, bladder displacement, and increased residual urine volume. Asymptomatic bacteriuria (ASB) during pregnancy can increase the risk of pyelonephritis and subsequent maternal and fetal complications. Pregnant women should be screened for ASB at least once at the beginning of pregnancy (aft er 14 weeks). E.coli is the dominant uropathogen in 70 – 95% of UTI cases in pregnant women. The main treatment for ABT and pyelonephritis in pregnancy (PiP) is antibiotic therapy (ABT), which is prescribed empirically in most cases. There is currently no consensus on the choice of ABT and the duration of treatment for UTI in pregnant women. In the case of ineff ective drug therapy of PiP, it is necessary to raise the issue of the upper urinary tract drainage promptly.